The impact of building information modeling (BIM) to architechtural design process - Rajendran, Punitha (2015)
Design in architecture is one of the most diverse activities considered by all related parties in construction industry. During the construction design process, many problems and errors such as design changes & rework, incomplete design, standard of quality in drawings and technical specifications, lack of communication, delays in the drawings, mistakes and errors are arising from this industry day by day. This research has been conducted with the aim to establish the contribution of Building Information modeling (BIM) on architectural design process. The objectives of this research includes, to recognize and examine the current conventional design problems in construction projects in terms of time, cost and quality and to recommend the benefit that is obtained by using BIM technology in the architectural design process. This research was conducted by using qualitative method where experience architects whom are currently implementing BIM in their firms was been interviewed. The feedback and results obtained from the interview were analyzed by using Microsoft Excel. Quota sampling method was used in selecting the respondents, which consists of 8 architects implementing BIM. The analysis results shows that, architect realize the problems and suggested the solutions based on their experience in handling several of projects by using the conventional method. It also shows that, BIM is the future tools for 3D design since it integrate all the design documents, the drawing are well interpreted and the designer easily viewable compared to conventional method. It is important, architects need to present their design in 3D drafting to create a better visualization to the client. Adoption of BIM should be implemented from the early process in order to manage construction project effectiveness.